Heterogeneous preferences for living in a hydrogen home: an advanced multigroup analysis - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Haq, Anwar Ul; Nabavi, Seyed Ali (Royal Society of Chemistry, 2024)
The UK Hydrogen Strategy (August 2021) and subsequent Heat and Buildings Strategy (October 2021) affirm that a strategic decision is set to be taken by 2026 on the prospect of residential decarbonisation via ‘hydrogen homes’. As this decision date draws nearer, quantitative insights on consumer perceptions of hydrogen-fuelled heating and cooking appliances remain limited. The existing knowledge deficit presents a substantial barrier to implementing a socially acceptable deployment pathway for residential decarbonisation. Despite recent efforts to advance the social science research agenda on hydrogen acceptance, few studies have advanced theoretical knowledge or pursued comprehensive statistical analyses. This study responds to the extant research gap by analysing the perceived adoption potential for hydrogen homes via partial least squares-necessary condition-multigroup analysis. Drawing on data from a nationally representative online survey (N = 1845) conducted in the UK, the adoption dynamics for domestic hydrogen are compared across four sub-groups of the population. The findings suggest that non-economic constructs such as safety perceptions and production perceptions are potentially more influential at this stage of the domestic hydrogen transition. Differences between consumer sub-groups are explained by safety, technology, and production perceptions, whereas financial perceptions are relatively homogeneous across the segments. These patterns underline the opportunity to strengthen residential decarbonisation efforts through segment-specific polices and strategic engagement with different parts of the housing stock. Policy makers and key stakeholders should factor consumer heterogeneity into net-zero decision-making processes by firstly acknowledging the amplifying effect of technology and environmental engagement in supporting adoption prospects for hydrogen homes. Socially acceptable strategies for decarbonising the residential sector can be supported by actively responding to heterogeneous household preferences for living in a hydrogen home.